ChemInform Abstract: Layered Molybdenum (Oxy)pyrophosphate a Cathode for Lithium‐Ion Batteries. Issue 46 (24th October 2013) - Wen, Bohua; Chernova, Natasha A.; Zhang, Ruibo; Wang, Qi; Omenya, Fredrick; Fang, Jin; Whittingham, M. Stanley
Abstract The layered compound δ‐(MoO2)2P2O7 is synthesized by heating MoO2HPO4·H2O (560 °C, 6 min).